2023
DOI: 10.1021/acsami.3c09197
|View full text |Cite
|
Sign up to set email alerts
|

In Situ-Generated Heat-Resistant Hydrogen-Bonded Organic Framework for Remarkably Improving Both Flame Retardancy and Mechanical Properties of Epoxy Composites

Yingbing Zou,
Wenqi Cui,
Denglong Chen
et al.

Abstract: In this study, the heat-resistant hydrogen-bonded organic framework (HOF) material HOF-FJU-1 was synthesized via in situ generation and then used as flame retardants (FRs) to improve the flame retardancy of epoxy resin (EP). HOF-FJU-1 can maintain high crystallinity at 450 °C and thus function as a flame retardant in EP. The study found that HOF-FJU-1 facilitates the improvement of char formation in EP, thus inhibiting heat transfer and smoke release during combustion. For EP/HOF-FJU-1 composites, the in situ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…It suggested that the combination of the polymer bulk and the nanofibrous structure in TLCP-N5 was conducive to the formation of a high-quality char layer, thus inhibiting the diffusion of oxygen and suppressing heat transfer during combustion . The degree of graphitization of TLCP residues was represented by the ratio of the integrated intensities of the D and G bonds (Figure F). ,, D and G bands, centered at 1360 and 1580 cm –1 in spectra, were associated with the vibration of carbon atoms in a disordered graphite structure and an ordered graphic structure, respectively. , Lower ratios of I D / I G of TLCP-N5 (1.12) than TLCP-N0 (1.44) indicated that TLCP-N5 possessed a higher graphitization degree and a more compact char layer. Thus, the condensation phase played a dominant role in the flame-retardant mechanism of TLCP-N5. The formation of a dense char layer during burning could inhibit the combustible gaseous release and heat exchange, which is shown in Figure G.…”
Section: Resultsmentioning
confidence: 99%
“…It suggested that the combination of the polymer bulk and the nanofibrous structure in TLCP-N5 was conducive to the formation of a high-quality char layer, thus inhibiting the diffusion of oxygen and suppressing heat transfer during combustion . The degree of graphitization of TLCP residues was represented by the ratio of the integrated intensities of the D and G bonds (Figure F). ,, D and G bands, centered at 1360 and 1580 cm –1 in spectra, were associated with the vibration of carbon atoms in a disordered graphite structure and an ordered graphic structure, respectively. , Lower ratios of I D / I G of TLCP-N5 (1.12) than TLCP-N0 (1.44) indicated that TLCP-N5 possessed a higher graphitization degree and a more compact char layer. Thus, the condensation phase played a dominant role in the flame-retardant mechanism of TLCP-N5. The formation of a dense char layer during burning could inhibit the combustible gaseous release and heat exchange, which is shown in Figure G.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to metal–organic frameworks (MOFs) which can combine with other frameworks to construct superior functional materials, HOFs have also formed composites successfully with metal ions, enzymes, metal nanoparticles, polymers and covalent organic frameworks (COFs). 39–43 The combination of HOFs and MOFs has been demonstrated to effectively address the limitations of each material while enhancing the overall performance through their mutual convertibility. However, due to the relatively short development time of HOFs, there is limited research on the combination of HOFs and MOFs.…”
Section: Introductionmentioning
confidence: 99%